2020
DOI: 10.1371/journal.pone.0241378
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-perceptive discrimination on fabric tactile stimulation by Electroencephalographic (EEG) spectra

Abstract: The precise evaluation of sensory perceptions during fabric-skin interactions is still poorly understood in neuroscience. This study aims to investigate the cortical sensory response to fabric stimuli with different textiles by Electroencephalographic (EEG) spectral intensities, and evaluate the relationships between EEG frequency bands, traditional subjective questionnaires, and the materials’ physical properties. Twelve healthy adult participants were recruited to test three fabrics with different textile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Theta oscillations could be instrumental in binding visuo-tactile information to increase touch sensation. This is supported by studies showing that higher amplitudes of theta oscillations encode for touch intensity (Michail et al, 2016), fabric physical properties (e.g., warmness, softness, overall comfort, Jiao et al, 2020) as well as for more salient sensory stimuli (Iannetti et al, 2008). The dynamic velvet-like visual feedback could have also primed tactile representation of the velvet fabric.…”
Section: Discussionmentioning
confidence: 72%
“…Theta oscillations could be instrumental in binding visuo-tactile information to increase touch sensation. This is supported by studies showing that higher amplitudes of theta oscillations encode for touch intensity (Michail et al, 2016), fabric physical properties (e.g., warmness, softness, overall comfort, Jiao et al, 2020) as well as for more salient sensory stimuli (Iannetti et al, 2008). The dynamic velvet-like visual feedback could have also primed tactile representation of the velvet fabric.…”
Section: Discussionmentioning
confidence: 72%
“…Contrary to previous studies, we have not observed changes in the gamma frequency band for electrode C3. These modulations have been associated with tactile processing in other tactile discrimination tasks (Michail et al, 2016;Jiao et al, 2020;Ross et al, 2022), tactile spatial attention (Bauer et al, 2006), and multisensory communication (Misselhorn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the theta frequency band in the parietal region has been reported to participate in the regulation of attention and emotion during tactile processing [31]. Gamma band oscillations in the primary somatosensory cortex have been associated with tactile processing in other tactile discrimination tasks [32,33], tactile spatial attention (namely, when simultaneous alpha and beta band suppression occurs in the parieto-occipital cortex) [34], and multisensory communication [35]. Here, no differences or signi cant changes in power were observed in the gamma frequency band for the C3/4 electrodes, possibly due to the long duration of the periods analyzed [13].…”
Section: Discussionmentioning
confidence: 99%